Towards a Secure Blockchain Ecosystem: Current Vulnerabilities and Future Directions in Smart Contract Security - Zhao Boya (ITM Web of Conferences)
As a distributed shared transaction ledger, blockchain technology has the characteristics of decentralization, immutable, irreversible and traceable, and is changing the inherent model of traditional industries. Smart contracts, as one of the core applications of blockchain technology, provide the basis for a variety of practical applications. However, the frequent security problems of smart contracts have not only caused huge economic losses, but also hindered the development of blockchain systems. According to relevant studies, the economic losses caused by smart contract security breaches have exceeded billions of dollars. Therefore, the security of smart contracts has become a hot topic at home and abroad. This study discusses the technical vulnerabilities and corresponding solutions of smart contracts from the code level. In-depth analysis of security vulnerabilities in smart contracts can help identify and repair potential security hazards, improve the overall security of contracts, and prevent the theft of funds or abnormal execution of contracts. By raising the security awareness of developers, enterprises and users, it is possible to promote the application of smart contracts in high-security fields such as finance and law and promote the healthy development of the blockchain ecosystem.